Himpunan pidato/pengarahan Gubernur KDH Tk. I Sumatera Utara - Nasution, Kaharudin (Biro Humasy Pemdasu, 1986)
Administrative and socioeconomic aspects of development in Sumatera Utara Province; collection of speeches of the governor.